Brachionium kirbyi, a new species honoring the founder of the “Bosque de Paz” Orchid Project in Costa Rica - Karremans Lok, Adam Philip (2015)
A new species of Brachionidium from Costa Rica is described and illustrated. Brachionidium kirbyi is most similar to Brachionidium dressleri Luer. It can be recognized by the erect plants, up to 14 cm tall, often branching, the greenish-yellow flowers, with a purplish-pinkish blotch at base of the dorsal sepal, the entire sepals, the petals that are not reflexed and the triangular lip.